Molecular intersections of traumatic brain injury and Alzheimer’s disease: the role of ADMSC-derived exosomes and hub genes in microglial polarization - Pengtao Li; Liguo Ye; Sishuai Sun; Yue Wang; Yihao Chen; Jianbo Chang; Rui Yin; Xiaoyu Liu; Wei Zuo; Houshi Xu; Xiao Zhang; Robert Chunhua Zhao; et al. (Metabolic Brain Disease, 2024)

Wave forces and dynamic pressures on pile-supported breakwaters with inclined perforated plates under regular waves - Ziwang Li; Rui Liu; Zhenlu Wang; Bingchen Liang; Haofeng Xia; Xuehai Sun; Xinpeng Wang; Luming Shi (Frontiers in Marine Science, 2024)
The use of pile-supported breakwaters can be a cost-effective solution for wave energy dissipation when traditional rubble mound breakwaters are not suitable. For a cost-effective design of these barriers, it is essential to obtain accurate estimates of dynamic pressures and wave forces. Laboratory experiments were conducted to investigate the dynamic pressures and forces on a novel pile-supported breakwater with inclined perforated plates. The analysis focused on various wave and structural parameters, including incident wave height, wave period, plate porosity, and plate configuration. For double-layer configurations with the same porosity, dynamic pressures on the single-layer or front plate were significantly higher than on the rear plate, with rear plate forces being 20% to 60% less. The dynamic pressure on the rear plate exhibited a uniform vertical distribution. Varying plate porosity at different locations significantly impacted structural forces. Gradually decreasing porosity improved wave dissipation and reduced forces on the plates, with front and back plate forces reaching approximately 70% of those on single-layer plates. Optimal protection across various wave periods can be achieved by adjusting porosity and plate arrangement. These findings provide valuable insights for designing pile-supported breakwaters in coastal protection engineering.

Stress response and adaptation mechanism of triploid rainbow trout (Oncorhynchus mykiss) treated with chronic heat challenge - Xiuhua Ma; Guoliang Sun; Yuqiong Meng; Jiao Li; Zezhong Wu; Rui Ma (Aquaculture, 2024)

Construction risk probability assessment of shield tunneling projects in karst areas based on improved two-dimensional cloud model - Huaiyuan Sun; Yi Rui; Yanyun Lu; Yiming Dai; Xiang Wang; Xiaojun Li (Tunnelling and Underground Space Technology, 2024)

Improving the affordability and reducing greenhouse gas emissions of the EAT-Lancet diet in China - Meng Li; Yanan Wang; Shunan Zhao; Wei Chen; Yu Liu; Heran Zheng; Zhongxiao Sun; Pan He; Rui Li; Sun Zhang; Peixue Xing; Qiao Li (Sustainable Production and Consumption, 2024)

Response of soil carbon and nitrogen stocks to irrigation - A global meta-analysis - Weihao Sun; Zhibin He; Dengke Ma; Bing Liu; Rui Li; Shuai Wang; Arash Malekian (Science of The Total Environment, 2024)

Recycled lithium battery nanomaterials as a sustainable nanofertilizer: Reduced peanut allergenicity and improved seed quality - Yaqi Jiang; Yi Sun; Pingfan Zhou; Guikai Zhu; Qibin Wang; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Science of The Total Environment, 2024)

Contribution of alkaline magmas to the petrogenesis of Triassic aluminous A-type granites on Liaodong Peninsula, Northeastern China - Yu-Sheng Zhu; Jin-Hui Yang; Jin-Feng Sun; Jing-Yuan Chen; Lei Xu; Rui Li; Bao-Quan Zhou (Lithos, 2024)

Application of metallic minerals in wastewater treatment: A review - Xuchao Sun; Yinghao Tang; Rui Li; Kaizhen Wu; Fang Shen; Shiping Zhang; Lutao Xue; Yu Jiang; Xiaoyong Wu (Journal of Water Process Engineering, 2024)

Deep learning-assisted detection of psychoactive water pollutants using behavioral profiling of zebrafish embryos - Ya Zhu; Lan Li; Shaokui Yi; Rui Hu; Jianjun Wu; Jinqian Xu; Junguang Xu; Qinnan Zhu; Shijia Cen; Yuxuan Yuan; Da Sun; Waqas Ahmad; et al. (Journal of Hazardous Materials, 2024)

Electrostatic self-assembly of hydrotalcite-based g-C3N4 composites for adsorption and photocatalytic degradation of aqueous norfloxacin - Xiaodong Yang; Minghui Li; Zhiyong Hou; Xuefei Yang; Yuanxia Guo; Shuaiqi Luo; Jin Zhao; Kai Wang; Pengkai Sun; Qiang Yang; Rui Chen; Shuo Yang; et al. (Journal of Environmental Chemical Engineering, 2024)

Effect of yeast (Saccharomyces cerevisiae) fermentation on conformational changes in pig liver proteins and their ability to bind to characteristic aldehydes - Jin Luo; Li Liang; Jingcheng Zhang; Yongzhao Bi; Rui Yang; Baoguo Sun; Yuyu Zhang (Food Chemistry, 2024)

Simple and rapid identification of beef within 30 min using a new food nucleic acid release agent combined with direct-fast qPCR - Yiyuan Yang; Jingnan Wang; Yajuan Sun; Huijie Chen; Hongri Zhao; Yongzhe Zhang; Peng Li; Changying Dong; Rui Yin (Food Chemistry, 2024)

Schisandrin A alleviates non-alcoholic fatty liver disease by improving liver metabolic disorders and suppressing the GSK3β signaling pathway - Li Zong; Rui Xu; Yunxia Sun; Junjie Qiu; Huihui Tao; Chengyu Shentu; Hongxia Niu; Tengfei Xu; Yuan Zhou (Food Bioscience, 2024)

Food web bioaccumulation model for ecological risk assessment of emerging organic pollutants in marine ecosystems: Principles, advances and challenges - Chuan-Sheng Sun; Rui Hou; Qian-Yi Huang; Zhi-Hua Li; Xiang-Rong Xu (Environmental Pollution, 2024)

Different polysaccharide-enhanced probiotic and polyphenol dual-functional factor co-encapsulated microcapsules demonstrate acute colitis alleviation efficacy and food fortification - Rui Sun; Zhongyi Lv; Ying Wang; Menghui Li; Jianrui Qi; Kai Wang; Haihua Yang; Tianli Yue; Yahong Yuan (Carbohydrate Polymers, 2024)

The Influence of pH on Sulfamethoxazole in Soil Systems: Migration and Degradation - Haifang Wang; Xin Li; Zhumei Sun; Xia Cao; Junli Zhang; Qihua Chen; Rui Ma (Water, Air, & Soil Pollution, 2024)

Deep Learning Based Diagnosis of Mild Cognitive Impairment Using Resting-State Functional MRI - Guangyao Li; Yalin Song; Huimin Liang; Xiaoman Sun; Junyang Yu; Rui Zhai; Mingyang Liang (Journal of Medical and Biological Engineering, 2024)

Tree characteristics, drought and microtopography modulate the response of subtropical Cunninghamia lanceolata to drought - Ruiting Liang; Yujun Sun; Zhaoting zhu; Rui Li (European Journal of Forest Research, 2024)

Identification and experimental validation of PYCARD as a crucial PANoptosis-related gene for immune response and inflammation in COPD - Rui Shi; Renwen Liang; Fang Wang; Lueli Wang; Wuyi Zidai; Jie Zhang; Luo Min; Xiaohua Du; Shibo Sun; Chuang Xiao; Chaozhong Li; Xuewu Liang; et al. (Apoptosis, 2024)

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

Comprehensive compositional analysis of liquid organic product prepared by industrialized hydrothermal cracking of biomass waste and its potential application as fertilizer - Rui Xia; Jue Wang; Xiao-xiao Yang; Qing-hai Li; Hui Zhou; Hui Sun; Yan-guo Zhang (Science of The Total Environment, 2024)

Long-term effects of conventional cultivation on soil cation exchange capacity and base saturation in an arid desert region - Dengke Ma; Zhibin He; Wenzhi Zhao; Rui Li; Weihao Sun; Wen Wang; Pengfei Lin; Lemin Wei; Wenliang Ju (Science of The Total Environment, 2024)

A novel AMSR2 retrieval algorithm for global C-band vegetation optical depth and soil moisture (AMSR2 IB): Parameters' calibration, evaluation and inter-comparison - Mengjia Wang; Philippe Ciais; Frédéric Frappart; Shengli Tao; Lei Fan; Rui Sun; Xiaojun Li; Xiangzhuo Liu; Huan Wang; Jean-Pierre Wigneron (Remote Sensing of Environment, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Effective strategy to improve nitrification inhibitor efficiency and minimize environmental risk with microenvironments created by ecofriendly biocomposites - Dongjia Li; Ting Yang; Qi Wang; Saihong Wang; Yingying Sun; Rui Liu; Deli Chen (Journal of Environmental Management, 2024)

Multi-omics analysis of five species of milk and specific composition links within each species - Qian Li; Xiaowei Wang; Qiu Zhang; Yanzhi Wu; Rui Chen; Yinggang Sun; Yuan Pan; Siyi Li; Zeying Wang (Food Chemistry, 2024)

Nitrogen reduction enhances crop productivity, decreases soil nitrogen loss and optimize its balance in wheat-maize cropping area of the Loess Plateau, China - Jinjin Wang; Rui Qian; Jiaxiang Li; Funan Wei; Zhimeng Ma; Sisi Gao; Xu Sun; Peng Zhang; Tie Cai; Xining Zhao; Xiaoli Chen; Xiaolong Ren (European Journal of Agronomy, 2024)

Rational design of pulse-electrolysis protocols promotes molten-salt electrorefining - Leyang Li; Ruiyang Sun; Rui Yuan; Manpeng Lin; Linlin Wang; Qi Wang; Jiguo Tu; Handong Jiao; Shuqiang Jiao (Chemical Engineering Journal, 2024)

Inflammatory microenvironment activation-targeted self-delivery nanomedicine for effective rheumatoid arthritis treatment - Xinrui Dong; Haibao Liu; Rui Sun; Shuwen Tan; Gaoyang Li; Xuerou Jin; Xiaoqin Zhang; Zhiyi Xiao; Dingxiang Li; Jun-Li Cao; Xiaoran Deng (Chemical Engineering Journal, 2024)

A photosensitive modification of recombinant Salmonella carrying shRNA-PD-L1 promotes host immunity against poorly immunogenic tumors - Jiaying Yang; Mei Yang; Qi Wang; Qian Luo; Yingtong Wang; Jicheng Sun; Jixuan Liu; Jiasi Chen; Juanjuan Mao; Hailin Yin; Dhan V. Kalvakolanu; Baofeng Guo; et al. (Chemical Engineering Journal, 2024)

Immunomodulatory hydrogel patches loaded with curcumin and tannic acid assembled nanoparticles for radiation dermatitis repair and radioprotection - Ruoyuan Huang; Wenjie Sun; Wenzhao Li; Rui Hu; Rui Meng; Zheng Peng; Rongbo Yang; Tianyu Huang; Jinhui Du; Luoran Shang; Congying Xie (Chemical Engineering Journal, 2024)

Surface segregation on Ag@MNi (M = Pd, Pt, Rh, and Ru) core–shell nanocrystals for enhancing the oxygen reduction performance - Xinyuan Zhou; Qiyan Sun; Xinlin Wang; Ruixue Zhang; Bin Li; Zexing Wu; Dehong Chen; Lei Wang; Guang-Rui Xu (Chemical Engineering Journal, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

“Four-in-One” multifunctional nanohybrids integrated magnetic colorimetric catalytic SERS-driven lateral flow immunoassay for ultrasensitive detection of MPXV - Xiaoxian Liu; Xingsheng Yang; Zongzheng Zhao; Xiao Li; Jing Liang; Yinuo Sun; Rui Xiao; Guanghui Wang (Chemical Engineering Journal, 2024)

A miniaturized microfluidic nanoplasmonic sensor with cavity reflection enhancement for ultrasensitive molecular interaction analysis - Hongli Fan; Mingqian Chen; Rui Li; Youqian Chen; Shaoqi Zeng; Wenjun Hu; Gang L. Liu; Chunmeng Sun; Liping Huang (Chemical Engineering Journal, 2024)

Phthalates on indoor surfaces and associated exposure via surface touch behavior: Observation in university dormitories and its implications - Fangzhou Yuan; Yu Sun; Na Li; Jianping Cao; Nan Zhang; Daniel Mmereki; Zhonghua Wei; Rui Chen; Jinyu Zhou; Yousheng Xu; Zhongming Bu (Building and Environment, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Deep structure of the Kumkol basin in the northern Tibetan Plateau and its resource environmental implications - Wenhui Li; Zhanwu Lu; Rui Gao; Xiaofan Deng; Jingyuan Li; Guangwen Wang; Zhanxuan Sun (Science China Earth Sciences, 2024)

Evaluation and fusion of multi-source sea ice thickness products with limited in-situ observations - Tongtong Li; Yangjun Wang; Bin Wang; Kefeng Liu; Xi Chen; Rui Sun (Frontiers in Marine Science, 2024)
Sea ice thickness (SIT) is a critical and sensitive parameter in the climate system, with its dynamic changes profoundly influencing global climate models, navigational routes, and the potential for Arctic resource development. Given the widespread application of current satellite remote sensing technology in monitoring SIT, significant uncertainties remain. This study first underscores the importance of in-situ observations as a direct measurement method for SIT. However, the limitations of in-situ data in terms of acquisition cost, spatiotemporal coverage continuity, and distribution uniformity significantly hinder the effective evaluation of multi-source SIT products. To address this, the study innovatively introduces the Triple Collocation (TC) method, which effectively mitigates the impact of errors from individual data sources on the overall evaluation results through a mutual validation mechanism among multiple satellite data sources. This allows for a scientific assessment of multi-source SIT products even in the context of scarce in-situ observations. The findings indicate that the TC method not only successfully resolves the challenges of multi-source data evaluation but also facilitates data integration among these products, significantly enhancing the overall accuracy and spatiotemporal consistency of SIT data.

Association Between Zinc Ion Concentrations in Seminal Plasma and Sperm Quality: A Chinese Cross-Sectional Study - Gangxin Chen; YeBin Feng; Rui Yang; Haiyan Li; Zhiqin Huang; Zhihao Li; Beihong Zheng; Yan Sun (Biological Trace Element Research, 2024)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

Nano Fe3O4 improved the electron donating capacity of dissolved organic matter during sludge composting - Liu Chen; Zeyu Zhang; Rui Yang; Xiaojie Wang; Jieyu Yu; Hong Jiang; Wenjie Zhang; Beidou Xi; Xiaojie Sun; Ningjie Li (Journal of Environmental Management, 2024)

Research progress and prospect of covalent organic frameworks (COFs) and composites: From synthesis to application in water contaminants - Rui Li; Fengfei Sun; Zhen Liu; Yuwei Shi; Sizhe He; Junfeng Chen (Journal of Environmental Chemical Engineering, 2024)

Thermo-economic analysis and multi-objective optimization of cryogenic CO2 capture systems based on liquefied natural gas cold energy utilization - Gequn Shu; Borui Liu; Hua Tian; Ligeng Li; Rui Sun; Xuan Wang (Journal of Environmental Chemical Engineering, 2024)

Efficient degradation of Rhodamine B by visible-light-driven biomimetic Fe(III) complex/peroxymonosulfate system: The key role of FeV=O - Chen-Xuan Li; Rui Wang; Wen Sun; Kangping Cui; Xian-Zhong Fu; Minshu Cui; Yihan Chen; Zhi Guo; Yingying Liu (Journal of Environmental Chemical Engineering, 2024)

Global estimates of ambient NO2 concentrations and long-term health effects during 2000–2019 - Wenwen Sun; Kuangyi Lu; Rui Li (Environmental Pollution, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Short-term exposure to ambient fine particulate matter constituents and myocardial infarction mortality - Yingxin Li; Bing Lu; Jing Wei; Qingqing Wang; Wancheng Ma; Rui Wang; Ruijun Xu; Zihua Zhong; Lu Luo; Xi Chen; Ziquan Lv; Suli Huang; et al. (Chemosphere, 2024)

HT-2 toxin impairs porcine oocyte in vitro maturation through disruption of endomembrane system - Jia-Rui Li; Si-Le Wu; Lin-Lin Hu; Bi-Yun Liao; Shao-Chen Sun (Theriogenology, 2024)

Associations between multiple urinary metals and metabolic syndrome: Exploring the mediating role of liver function in Chinese community-dwelling elderly - Yuqing Dai; Siyu Duan; Rui Wang; Pei He; Zhongyuan Zhang; Meiyan Li; Zhuoheng Shen; Yue Chen; Yi Zhao; Huifang Yang; Xiaoyu Li; Rui Zhang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Constructing interfacial chemical interaction of dual-carbon protected cobalt diselenide anode for sodium storage - Xiaoying Liu; Dongdong Xue; Rui Ren; Ting Ou; Tao Sun; Yuchen Han; Fan Jin; Yannan Li; Yan Zhao; Jiangwei Zhang (Chemical Engineering Journal, 2024)

Efficient elimination of antibiotic resistome in livestock manure by semi-permeable membrane covered hyperthermophilic composting - Bo Sun; Zhihui Bai; Rui Li; Manjiao Song; Jian Zhang; Jiancheng Wang; Xuliang Zhuang (Bioresource Technology, 2024)

Global health benefits of shipping emission reduction in early 2020 - Wenwen Sun; Wenxin Jiang; Rui Li (Atmospheric Environment, 2024)

Green Approach for Simultaneous Quantitative Analysis of Fluoroquinolones in the Environment using Three-Dimensional Fluorescence Coupled with Second-Order Calibration Method - Yuping Yao; Liyan Song; Lingli Jiang; Mengfan Sun; Rui Li; Zhongze Zhou; Yuanna Li (Journal of Fluorescence, 2024)

Full title: The performance evaluation of marine ecological civilization construction (MECC): A case study of coastal cities in Jiangsu Province, China - Yang Yang; Dingwu Liu; Rui Xu; Zhuona Li; Chenwei Shi; Xiaodong Zhu; Xiang Sun (Ocean & Coastal Management, 2024)

Feasibility of nanofiltration process for efficient separation of gallic acid from the extract of black tea in aqueous solution - Yiwei Dong; Rui Zhao; Chunyan Xu; Jinxin Liu; Zhiguo Dong; Ziqi Chen; Jinfeng He; Chuanrun Li; Haiyang Yan; Li Sun (Journal of Water Process Engineering, 2024)

Ultra-high capacity and anti-interference for Cr(VI) removal by tannin-polyvinylimine modified graphite carbon nitride - Wen Sun; Rui Wang; Lingfei Li; Jun Zhao; Bianhua Liu (Journal of Environmental Chemical Engineering, 2024)

Highly selective and sensitive immunoassays for flurogestone acetate analysis in goat milk: From rational hapten design and antibody production to assay development - Rui Liu; Xingya Sun; Yingjie Zhang; Peipei Li; Li Nan; Qing Shen; Kai Wen; Xuezhi Yu; Jianzhong Shen; Yantong Pan; Zhanhui Wang (Food Chemistry, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Recombinant protein transaldolase of Bifidobacterium bifidum E3 and its anti-inflammatory activity - Rui Yang; Jiayu Zhang; Ting Cao; Yifan Zhang; Junwu Cai; Lenan Sun; Yingxue Yue; Bailiang Li; Guicheng Huo (Food Bioscience, 2024)

Effectiveness of thinning in mitigating post-drought legacy effects on Chinese fir in subtropical plantation forests, Southeastern China - Ruiting Liang; Yifu Wang; Yujun Sun; Zhaoting zhu; Rui Li (Dendrochronologia, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

Sub-daily live fuel moisture content estimation from Himawari-8 data - Xingwen Quan; Rui Chen; Marta Yebra; David Riaño; Víctor Resco de Dios; Xing Li; Binbin He; Rachael H. Nolan; Anne Griebel; Matthias M. Boer; Yuanqi Sun (Remote Sensing of Environment, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Electrochemiluminescence detection of diazinon in vegetables based on the synergistic interaction of WO3-x dots with Au@SiO2 nanocapsules - Wenzheng Liu; Haifang Wang; Peisen Li; Chengqiang Li; Donghan Li; Zhenying He; Yuhao Zhang; Jingcheng Huang; Jin Hua; Rui Xu; Lianming Xia; Yemin Guo; et al. (Food Chemistry, 2024)

CaO/SiC alkaline fillers for High-Temperature reduction of mercury (II) - Haiyang Li; Lina Sun; Xiaoshuo Liu; Jiangyi Tong; Yuxing Zhou; Rui Jin; Yufeng Duan; Haitao Hu (Chemical Engineering Journal, 2024)

Reindeer (Rangifer tarandus) hindlimb joint kinetics: propulsive and energy storage mechanisms and mechanical work - Guoyu Li; Rui Zhang; Hao Pang; Junfeng Wang; Dan Jin; Xumin Sun; Dianlei Han; Zhisong Li; Lige Wen (Polar Biology, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

Individual and joint associations of per- and polyfluoroalkyl substances (PFAS) with gallstone disease in adults: A cross-sectional study - Tianshan Shi; Di Li; Donghua Li; Jin Sun; Peng Xie; Tingrong Wang; Rui Li; Zhenjuan Li; Zixuan Zou; Xiaowei Ren (Chemosphere, 2024)

Physiological and molecular mechanism of Populus pseudo-cathayana × Populus deltoides response to Hyphantria cunea - Yutong Ding; Jiajia Shen; Hanxi Li; Yue Sun; Tingbo Jiang; Xiangbo Kong; Rui Han; Chunli Zhao; Xinxin Zhang; Xiyang Zhao (Pesticide Biochemistry and Physiology, 2024)

Various functions of detoxification enzymes against insecticides in Nilaparvata lugens selected by toxicity assays and RNAi methods - Jun Yang; Li-Yuan Sun; Ruiyan Ma; Rui Tang; Juan-Ying Zhao; Qing-Nian Cai (Pesticide Biochemistry and Physiology, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Synthesis, characterization, and environmental evaluation of Fe-PCN-134: A mixed-linker metalloporphyrin MOF for the degradation of atrazine via visible photo-Fenton reaction - Meng Yu; Yinmin Wang; Yingjian Ma; Zhe Sun; Li Ma; Shouhe Pan; Rui Zhao; Xinyu Guo; Yong Xu; Xuemin Wu (Journal of Environmental Chemical Engineering, 2024)

MOF derived highly dispersed bimetallic Fe-Ni nitrogen-doped carbon for enhanced peroxymonosulfate activation and tetracycline degradation - Lingyun Jing; Shasha Liu; Tong Wang; Zeqiang Zhang; Xia Zhao; Zhili Sun; Pengbo Hao; Yeqiang Hu; Wenhan Yang; Rui Quan; Xinyong Li; Dongnian Zhang; et al. (Journal of Environmental Chemical Engineering, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Variations in antibiotic resistomes associated with archaeal, bacterial, and viral communities affected by integrated rice-fish farming in the paddy field ecosystem - Yiran Hou; Weixu Diao; Rui Jia; Wei Sun; Wenrong Feng; Bing Li; Jian Zhu (Environmental Research, 2024)

Comparative steroidogenic effects of hexafluoropropylene oxide trimer acid (HFPO-TA) and perfluorooctanoic acid (PFOA): Regulation of histone modifications - Fuping Li; Rui Yang; Lu Lu; Weizhen Hua; Yan Sun; Meiping Tian; Yanyang Lu; Qingyu Huang (Environmental Pollution, 2024)

Composite porous 3D foam for solar-driven atmospheric water harvesting in low humidity natural environment - Jiyan Li; Guoyu Xing; Min Qiao; Silu Du; Tao Zhou; Shuo Gao; Hanxue Sun; Rui Jiao; An Li (Chemical Engineering Journal, 2024)

C@MOF composite material for rapid and efficient capture of gaseous iodine - Rui-Li Yu; Mei-Qi Sun; Xiao-Yu Wang; Dao-Tong Li; Zhen-Le Li; Liang-Zhi Xia (Chemical Engineering Journal, 2024)

Genome-wide identification and expression-pattern analysis of sulfate transporter (SULTR) gene family in cotton under multiple abiotic stresses and fiber development - Yu Chen; Xianghui Xiao; Rui Yang; Zhihao Sun; Shuhan Yang; Haibo Zhang; Baoguang Xing; Yanfang Li; Qiankun Liu; Quanwei Lu; Yuzhen Shi; Youlu Yuan; et al. (Functional & Integrative Genomics, 2024)

Investigation of the effects and mechanisms of manganese-based NMs on rice growth - Yaqi Jiang; Yi Sun; Peng Zhang; Pingfan Zhou; Qibin Wang; Guikai Zhu; Weichen Zhao; Yuanbo Li; Quanlong Wang; Yukui Rui (Environmental Science and Pollution Research, 2024)

Morphological estimation of primary branch length of individual apple trees during the deciduous period in modern orchard based on PointNet++ - Xiaoming Sun; Leilei He; Hanhui Jiang; Rui Li; Wulan Mao; Dong Zhang; Yaqoob Majeed; Nikita Andriyanov; Vladimir Soloviev; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Biomineralization of phosphorus during anaerobic treatment of distillery wastewaters - Lei Zhang; Yiyang Yuan; Chengyuan Li; Yingdi Zhang; Huijuan Sun; Rui Xu; Yang Liu (Science of The Total Environment, 2024)

Cytotoxic withanolides from the stems and leaves of Physalis ixocarpa - Ke Xiang; Yan Liu; Rui Zhu; Yang Xu; Dejuan Sun; Yueying Yang; Yushu Yan; Bingyou Yang; Hua Li; Lixia Chen (Food Chemistry, 2024)

Effects of plastic film mulching on yield, water use efficiency, and nitrogen use efficiency of different crops in China: A meta-analysis - Tiantian Huang; Qianxiang Wu; Yangyang Yuan; Xintong Zhang; Ruiqi Sun; Rui Hao; Xiaohua Yang; Congfeng Li; Xiaoliang Qin; Fangqi Song; Charles O. Joseph; Wen Wang; et al. (Field Crops Research, 2024)

Hollow glass microspheres incoporated conjugated microporous polymers composite aerogels for sustainable evaporation - Jiaxuan Zhou; Xiaoyin Cao; Yanju Jing; Jia Zhang; Hanxue Sun; Jiyan Li; Rui Jiao; An Li (Chemical Engineering Journal, 2024)

ZnS-coated Yb3+-doped perovskite quantum dots: A stable and efficient quantum cutting photon energy converter for silicon-based electronics - Yue Wang; Nan Ding; Donglei Zhou; Wen Xu; Rui Sun; Wei Li; Yuqi Wang; Liheng Sun; Songtao Hu; Hongwei Song (Chemical Engineering Journal, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Hypoxia preconditioning of human amniotic mesenchymal stem cells enhances proliferation and migration and promotes their homing via the HGF/C-MET signaling axis to augment the repair of acute liver failure - Qian Wang; Yuwen Li; Hui Yuan; Linya Peng; Zixing Dai; Ye Sun; Rui Liu; Wenting Li; Jun Li; Chuanlong Zhu (Tissue and Cell, 2024)

Generation of tau dephosphorylation-targeting chimeras for the treatment of Alzheimer’s disease and related tauopathies - Jingfen Su; Yue Xiao; Linyu Wei; Huiyang Lei; Fei Sun; Weixia Wang; Jun Yin; Rui Xiong; Shihong Li; Pei Zhang; Ying Zhou; Xiaochuan Wang; et al. (Science Bulletin, 2024)

Competition between ocean thermal structure and tropical cyclone characteristics modulates ocean environmental responses in the Yellow and Bohai Seas - Xiuting Wang; Jiagen Li; Liang Sun; Mengyuan Xu; Haihua Liu; Rui Liu (Marine Environmental Research, 2024)

Association between ambient PM1 and the prevalence of chronic kidney disease in China: A nationwide study - Rui Chen; Chao Yang; Yuming Guo; Gongbo Chen; Shanshan Li; Pengfei Li; Jinwei Wang; Ruogu Meng; Huai-yu Wang; Suyuan Peng; Xiaoyu Sun; Fulin Wang; et al. (Journal of Hazardous Materials, 2024)

Constructing of Fe-Cu bimetallic MOFs derived electro-Fenton cathode for efficient norfloxacin removal - Yixin Du; Zhenpeng Li; Rui Feng; Qing Liu; Yanming Yang; Meng Sun; Yanxia Zhao; Tao Yan; Liangguo Yan (Journal of Environmental Chemical Engineering, 2024)

Sulfate radical-assisted photocatalytic degradation of quinoline with WO3/CuFe2O4/Cu Z-scheme system: Comparison of persulfate and sulfite activation - Bihan Sun; Houfen Li; Rong Han; Cong Gao; Rui Li; Aijuan Zhou; Xiuping Yue (Journal of Environmental Chemical Engineering, 2024)

Experimental analysis of a CO2 closed heat pump drying system combined with rotary dehumidification for drying banana slices drying - Zhili Sun; Qianqian Wang; Yingying Yuan; Dandan Wang; Qiang Zhou; Chunwei Xu; Kexin Meng; Haowei Peng; Lei Yan; Rui Jin; Lei Li; Haowei Liu; et al. (International Journal of Refrigeration, 2024)

A colorimetric and NIR fluorescent probe for ultrafast detecting bisulfite and organic amines and its applications in food, imaging, and monitoring fish freshness - Keli Zhong; Yang Li; Xiaoling Hu; Yangyang Li; Lijun Tang; Xiaofei Sun; Xuepeng Li; Jinglin Zhang; Yuqiong Meng; Rui Ma; Shulin Wang; Jianrong Li (Food Chemistry, 2024)

The prolamins, from structure, property, to the function in encapsulation and delivery of bioactive compounds - Xinmei Sha; Haili Sun; Yue Li; Jincan Wu; Haotong Zhang; Rui Yang (Food Hydrocolloids, 2024)

Enhanced photogenic self-cleaning of superhydrophilic Al2O3@GO-TiO2 ceramic membranes for efficient separation of oil-in-water emulsions - Dongdong Wang; Likun Huang; Haiyang Sun; Shaofang Li; Guangzhi Wang; Rui Zhao; Simin Zhou; Xiyu Sun (Chemical Engineering Journal, 2024)

Correlation and interaction between urinary metals level and diabetes: A cross sectional study of community-dwelling elderly - Rui Wang; Pei He; Siyu Duan; Zhongyuan Zhang; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Xiaoyu Li; Yanan Song; Yiping Sun; Rui Zhang; Jian Sun; et al. (Exposure and Health, 2024)

The SIDT2/MDA5/IFN axis contributes to virus resistance in teleost fish - Yaoguo Li; Hao Tang; Mingxue Sun; Qiaolin Liu; Yijing Liao; Hong Luo; Rui Li; Ronghua Wang; Hong Yang; Hongquan Wang; Jun Zou; Tiaoyi Xiao (Aquaculture, 2024)

A new perspective on anthropogenic nitrogen loss mitigation strategies: Integrated control via sustainable regional integration - Zeqian Zhang; Lihui Sun; Chenning Deng; Li Dong; Rui Xu; Chong Nie; Queping Yang (Science of The Total Environment, 2024)

The transmission of isotopic signals from precipitation to groundwater and its controls: An experimental study with soil cylinders of various soil textures and burial depths in a monsoon region - Ying Jiang; Jie Li; Rui Zuo; Congjian Sun; Yuanzheng Zhai; Lijun Tian; Wei Dai; Shufang Wang; Ziqi Shang; Yulian Liu; Xuan Jiao; Yuxi Xie; et al. (Journal of Hydrology, 2024)

Quantitative identification of the co-exposure effects of e-waste pollutants on human oxidative stress by explainable machine learning - Luhan Yang; Tao Zhang; Yanxia Gao; Dairui Li; Rui Cui; Cheng Gu; Lei Wang; Hongwen Sun (Journal of Hazardous Materials, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Activated carbon fibers functionalized with superhydrophilic coated pDA/TiO2/SiO2 with photoluminescent self-cleaning properties for efficient oil-water separation - Dongdong Wang; Likun Huang; Hanxiao Fang; Shaofang Li; Guangzhi Wang; Simin Zhou; Rui Zhao; Xiyu Sun (Journal of Hazardous Materials, 2024)

Engineering extracellular electron transfer to promote simultaneous brewing wastewater treatment and chromium reduction - Deguang Wu; Baocai Zhang; Sicheng Shi; Rui Tang; Chunxiao Qiao; Teng Li; Jichao Jia; Meiyi Yang; Xiaoguang Si; Yifei Wang; Xi Sun; Dongguang Xiao; et al. (Journal of Hazardous Materials, 2024)

Factors affecting chemical and textural properties of dried tuber, fruit and vegetable - Yue Li; Han Zhao; Kexin Xiang; Dajing Li; Chunju Liu; Haiou Wang; Wenqian Pang; Liying Niu; Rui Yu; Xiyun Sun (Journal of Food Engineering, 2024)

Arbuscular mycorrhizal fungi offset NH3 emissions in temperate meadow soil under simulated warming and nitrogen deposition - Nan Cui; Stavros Veresoglou; Yibo Tian; Rui Guo; Lei Zhang; Li Jiang; Furong Kang; Weizhe Yuan; Dan Hou; Lianxuan Shi; Jixun Guo; Mingzhou Sun; et al. (Journal of Environmental Management, 2024)

Effect of carbon modifier on characteristics and catalytic properties of zeolite–carbon hybrid supported Zr towards γ-valerolactone production - Zhongdi Liu; Rui Zhang; Huai Liu; Junhua Zhang; Yong Sun; Naya Li; Lincai Peng (Fuel, 2024)

Equilibrating provincial carbon increments for residential buildings in China under carbon peaking constraints - Liu Chen; Rui Li; Jinbo Zhang; Weiguang Cai; Kaiqiang Zhang; Yida Sun (Environmental Impact Assessment Review, 2024)

Excellent solar-driven interface evaporation by an oil repellence Janus photothermal membrane for oily wastewater treatment - Wenwen Luo; Jia Zhang; Meichen Liu; Anli Yi; Rui Jiao; Zhaoqi Zhu; Jiyan Li; Hanxue Sun; An Li (Chemical Engineering Journal, 2024)

Fucosylated chondroitin sulfate from sea cucumber Stichopus chloronotus alleviate the intestinal barrier injury and oxidative stress damage in vitro and in vivo - Huanan Yin; Rui Li; Jing Liu; Yanying Sun; Lei Zhao; Jiaojiao Mou; Jie Yang (Carbohydrate Polymers, 2024)

Structural characterization and osteogenic differentiation-promoting activity of polysaccharide purified from Chroogomphus rutilus - Ying Zhou; Lanzhou Li; Zhen Sun; Rui Liu; Yanfeng Zhu; Jingzheng Yi; Yutong Li; Min Hu; Di Wang (Carbohydrate Polymers, 2024)

Scientometric analysis of electrocatalysis in wastewater treatment: today and tomorrow - Qianqian Li; Xiaoya Fang; Lili Jin; Xiangzhou Sun; Hui Huang; Rui Ma; Han Zhao; Hongqiang Ren (Environmental Science and Pollution Research, 2024)

Water Properties and Diffusive Convection in the Canada Basin - Ling Qu; Shuangxi Guo; Shengqi Zhou; Yuanzheng Lu; Mingquan Zhu; Xianrong Cen; Di Li; Wei Zhou; Tao Xu; Miao Sun; Rui Zeng (Journal of Marine Science and Engineering, 2024)
The aim of this study is to better understand diffusive convection (DC) and its role in the upper ocean dynamic environment and sea ice melting in the Canada Basin. Based on a moored dataset with 6737 profiles collected from August 2003 to August 2011 in the upper layer of the Canada Basin, DC between the warm and salty Atlantic Water (AW) and the colder and less salty Lower Halocline Water (LHW) were investigated. The moorings were designated at four stations: A, B, C, and D, located at the southwestern, southeastern, northeastern, and northwestern parts of the basin, respectively. During the observation period, the temperature, salinity, and depth of the AW and LHW exhibited unique temporal variations. The temperature and salinity of the AW varied among stations, with a decreasing trend from northwest to southeast, consistent with the propagation path of the AW in the Canada Basin. The temperature and salinity of the LHW were similar at all stations. The AW and LHW cores were located between depths of 320–500 m and 160–300 m, respectively, and both gradually deepened over time. Distinct DC staircase structures were observed between the AW and LHW, more pronounced at stations C and D than at stations A and B, which is speculated to be related to eddies at stations A and B during the observation period. The vertical heat fluxes through the DC staircase layer at stations C and D (FHc_C and FHc_D) were estimated using an empirical formula. FHc_C ranged from 0.05 to 0.94 W/m2, and FHc_D ranged from 0.05 to 0.6 W/m2, with the maximum probability value for both at approximately 0.2 W/m2. The effective diffusivities at these two stations (KT_C and KT_D) are similar, ranging from 2 × 10−6 to 3 × 10−5 m2/s, with the highest probability occurring at 6 × 10−6 m2/s. Both the probability density function of the heat flux and the effective diffusivity skewed towards larger values and obey a lognormal distribution, indicating turbulence intermittency of the DC staircase in the Canada Basin. These finding offers new insights into the heat transport and turbulence in the DC staircase, and then bring a deeper understanding of sea ice melting in the Canada Basin.

Improved binocular localization of kiwifruit in orchard based on fruit and calyx detection using YOLOv5x for robotic picking - Changqing Gao; Hanhui Jiang; Xiaojuan Liu; Haihong Li; Zhenchao Wu; Xiaoming Sun; Leilei He; Wulan Mao; Yaqoob Majeed; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Characterization of emopamil binding protein (Cs-ebp) reveals its potential role in cholesterol biosynthesis and growth performance of Chinese tongue sole - Zhangfan Chen; Xihong Li; Peng Cheng; Jiaqi Mai; Yuqi Sun; Jiacheng Wang; Rui Shi; Qi Zhang; Na Wang; Songlin Chen (Aquaculture, 2024)

Regional background ozone estimation for China through data fusion of observation and simulation - Zhixu Sun; Jiani Tan; Fangting Wang; Rui Li; Xinxin Zhang; Jiaqiang Liao; Yangjun Wang; Ling Huang; Kun Zhang; Joshua S. Fu; Li Li (Science of The Total Environment, 2024)

Satellite observed aboveground carbon dynamics in Africa during 2003–2021 - Mengjia Wang; Philippe Ciais; Rasmus Fensholt; Martin Brandt; Shengli Tao; Wei Li; Lei Fan; Frédéric Frappart; Rui Sun; Xiaojun Li; Xiangzhuo Liu; Huan Wang; et al. (Remote Sensing of Environment, 2024)

Efficient benzo(a)pyrene degradation by coal gangue-based catalytic material for peroxymonosulfate activation - Chunquan Li; Shuaijun Yin; Yutong Yan; Chao Liang; Qingshui Ma; Rui Guo; Yubo Zhang; Jiushuai Deng; Zhiming Sun (Journal of Environmental Management, 2024)

Experimental and numerical research on the failure pattern and mechanisms of granite disc with a pre-crack after heating and liquid nitrogen cooling - Yuliang Zhang; Guowei Ma; Qiang Sun; Zhenlong Ge; Xindong Wei; Zhe Li; Fuxin Rui (International Journal of Rock Mechanics and Mining Sciences, 2024)

High temperature reduction of divalent mercury to elemental mercury for Hg-CEMS - Haiyang Li; Lina Sun; Xiaoshuo Liu; Xunlei Ding; Ao Shen; Rui Jin; Jiangyi Tong; Haitao Hu; Yufeng Duan (Fuel, 2024)

Differentiation of antioxidants in reducing oxidation and improving quality of ready-to-eat roasted shrimp after thermal sterilization - Shuo Wang; Songyi Lin; Rui Liang; Kexin Liu; Xiuhan Chen; Lei Chen; Shuang Li; Na Sun (Food Chemistry, 2024)

GC-IMS determination of volatile organic compounds as potential indicators of wheat germination rate - Yu Liu; Shuwei Ren; Qianqian Sun; Boli Guo; Yingquan Zhang; Ming Li; Rui Zhang (Food Bioscience, 2024)

Exploring the potential of a new marine bacterium associated with plastisphere to metabolize dibutyl phthalate and bis(2-ethylhexyl) phthalate by enrichment cultures combined with multi-omics analysis - Yueling Sun; Ying Zhang; Yongzheng Ma; Rui Xin; Xiaofeng Li; Zhiguang Niu (Environmental Pollution, 2024)

Anti-inflammasome bio-heterojunction (AI-bioHJ): Revolutionizing diabetic wound healing with in situ self-transformation and programmed gas therapy - Fan Yang; Rui Shu; Bin Li; Wenyu Dai; Wanxi Chen; Jiamin Sun; Ding Bai; Weizhong Yang; Yi Deng (Chemical Engineering Journal, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Assessing the impact of COVID-19 lockdown on fine-scale air quality across a heavy-pollution city using low-cost sensors - Wenwen Sun; Rui Li (Atmospheric Environment, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Effect of different water and organic matter content on the resistivity of loess - Rui Lv; Qiang Sun; Pengfei Li; Jishi Geng; Yuan Xin; Shaofei Wang (Science of The Total Environment, 2024)

Forager-farmer transition at the crossroads of East and Southeast Asia 4900 years ago - Minmin Ma; Minxia Lu; Rui Sun; Zhonghua Zhu; Dorian Q. Fuller; Jianxin Guo; Guanglin He; Xiaomin Yang; Lingling Tan; Yongxiu Lu; Jiajia Dong; Ruiliang Liu; et al. (Science Bulletin, 2024)

Revealing the membrane fouling behavior and interfacial interaction mechanism in a combined visible light photocatalysis-ultrafiltration system for advanced purification of NOM - Rui Yu; Yanling Yang; Liping Tian; Xing Li; Chunjiao Liu; Tianjie Sun; Haiqing Chang; Zhiwei Zhou (Journal of Water Process Engineering, 2024)

Inactivation of pathogenic microorganisms in water by electron beam excitation multi-wavelength ultraviolet irradiation: Efficiency, influence factors and mechanism - Yong-Qiang Li; Rui Sun; Chong-Miao Zhang; Zi-Xuan Liu; Rui-tao Chen; Jian Zhao; Hua-dong Gu; Huan-Cai Yin (Journal of Environmental Management, 2024)

Revisiting the porter hypothesis within the economy-environment-health framework: Empirical analysis from a multidimensional perspective - Xialing Sun; Rui Zhang; Zhaofeng Yu; Shichao Zhu; Xiaotong Qie; Jiaxi Wu; Pengpeng Li (Journal of Environmental Management, 2024)

A portable on-demand therapeutic nitric oxide generation apparatus: New strategy for diabetic foot ulcers - Huihui Bian; Junjie Wang; Xiaodong Shan; Xiuqing Li; Yongjin Wang; Rui Sun; Chongxian Wang; Juan Lv; Chunlei Xing; Chunlei Hui; Dinglei Zhang; Chenxi Zhang; et al. (Chemical Engineering Journal, 2024)